2013
DOI: 10.1002/ijc.28138
|View full text |Cite
|
Sign up to set email alerts
|

CADM1andMALpromoter methylation levels in hrHPV-positive cervical scrapes increase proportional to degree and duration of underlying cervical disease

Abstract: Combined detection of cell adhesion molecule 1 (CADM1) and T-lymphocyte maturation-associated protein (MAL) promoter methylation in cervical scrapes is a promising triage strategy for high-risk human papillomavirus (hrHPV)-positive women. Here, CADM1 and MAL DNA methylation levels were analysed in cervical scrapes of hrHPV-positive women with no underlying high-grade disease, high-grade cervical intraepithelial neoplasia (CIN) and cervical cancer. CADM1 and MAL methylation levels in scrapes were first related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
132
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 35 publications
21
132
1
Order By: Relevance
“…These results correspond to the finding that only a subset of CIN2/3 will progress to cancer over a long time period [18,19]. Previous studies on copy number changes and DNA methylation levels of only a few genes also showed a cancer-like profile in only a subset of CIN2/3 lesions [11,14,20,21]. These lesions were characterized by a preceding hrHPV infection of >5 years and considered as more advanced lesions, which have a high short-term progression risk to cancer.…”
Section: Discussionsupporting
confidence: 87%
“…These results correspond to the finding that only a subset of CIN2/3 will progress to cancer over a long time period [18,19]. Previous studies on copy number changes and DNA methylation levels of only a few genes also showed a cancer-like profile in only a subset of CIN2/3 lesions [11,14,20,21]. These lesions were characterized by a preceding hrHPV infection of >5 years and considered as more advanced lesions, which have a high short-term progression risk to cancer.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, FAM19A4 methylation analysis tested positive in all cervical scrapes of women with CIN3 lesions with a duration of the associated HPV infection of >5 years 22. Those lesions are characterized by a ‘cancer‐like’ (epi)genetic profile and have therefore been considered as advanced precancers 22, 28. Based on this feature, triage testing by methylation analysis has been proposed to confer a high reassurance against short‐term risk of cervical cancer 12.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, host cell methylation analysis of CADM1, MAL, mir124-2, and FAM19A4 in cervical scrapes allows the discrimination of high-grade CIN with a long-term preceding hrHPV-infection from those with a short-term hrHPV infection [95,96]. Concordantly, in both cervical scrapes and selfsampled cervicovaginal lavages, methylation levels of FAM19A4 have been shown to correspond with the estimated CIN lesion volume [100].…”
Section: 22mentioning
confidence: 85%
“…In both cervical scrapes and lavages the NPVs of CADM1/ MAL and FAM19A4(/mir124-2) methylation analysis (86.3-95.3%) are below the suggested 98% threshold [38]. However, given that methylation analysis of CADM1/MAL and FAM19A4(/mir124-2) has a very high sensitivity for carcinomas and CIN3 with a long-term previous hrHPV-infection [95,96], we argue that methylation-negative CIN3 lesions have a low short-term risk of progression to cancer. From this point of view, one might consider the use of (CADM1/MAL and FAM19A4(/mir124-2)) methylation analysis for triage of hrHPVpositive women accepting a somewhat lower NPV, thereby allowing CIN2/3 with low short-term progression risk to remain undetected.…”
Section: Expert Commentarymentioning
confidence: 90%
See 1 more Smart Citation